2018
DOI: 10.1021/jacs.8b07803
|View full text |Cite
|
Sign up to set email alerts
|

Free Amino Acid Recognition: A Bisbinaphthyl-Based Fluorescent Probe with High Enantioselectivity

Abstract: A novel fluorescent probe based on a bisbinaphthyl structure has been designed and synthesized. This compound in combination with Zn­(II) has exhibited highly enantioselective fluorescence enhancement with 13 common free amino acids. For example, its enantiomeric fluorescent enhancement ratios (ef or ΔI L/ΔI D) in the presence of the following amino acids are extremely high: 177 for valine, 199 for methionine, 186 for phenylalanine, 118 for leucine, and 89 for alanine. The observed high enantioselectivity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(73 citation statements)
references
References 34 publications
1
71
0
1
Order By: Relevance
“…[1][2][3] They also serve as important synthons andc hirality sourcesf or diversef unctional organic molecules. [6,7] The use of fluorescence in chiral recognition not only provides rapid analysis of the chiral composition of the substrates, [8] but maya lso allow direct imagingo ft he enantiomers of amino acids in cells. [6,7] The use of fluorescence in chiral recognition not only provides rapid analysis of the chiral composition of the substrates, [8] but maya lso allow direct imagingo ft he enantiomers of amino acids in cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] They also serve as important synthons andc hirality sourcesf or diversef unctional organic molecules. [6,7] The use of fluorescence in chiral recognition not only provides rapid analysis of the chiral composition of the substrates, [8] but maya lso allow direct imagingo ft he enantiomers of amino acids in cells. [6,7] The use of fluorescence in chiral recognition not only provides rapid analysis of the chiral composition of the substrates, [8] but maya lso allow direct imagingo ft he enantiomers of amino acids in cells.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] In recent years, the development of fluorescent molecular probes to discriminate the enantiomerso fa minoa cids hasr eceived significant attention. [6,7] The use of fluorescence in chiral recognition not only provides rapid analysis of the chiral composition of the substrates, [8] but maya lso allow direct imagingo ft he enantiomers of amino acids in cells. [6l] Previously,w ereported that (S)-3,3'diformyl-1,1'-bi-2-naphthol ((S)-1), in combination with Zn 2 + , could be used to conduct fluorescent discrimination of the enantiomers of functional amines, including severala mino acids, in methanol.…”
Section: Introductionmentioning
confidence: 99%
“…We prepared compound 1,a2,6-dibromomethylp yridine with ah ighly fluorinated alkyl chain, as ap recursort oaf luorophilic probe (Scheme 1). Reaction of 1 with the 1,1'-binaphthyl-based aldehyde (R)-2 8 in the presence of base followed by acidic deprotection gave the bis(binaphthyl) compound (R,R)-3.T his compound was found to be soluble in af luorous solvent 1H,1H,2H,2H-perfluoro-1-octanol( PFOH)a nd showed no fluorescence in this solvent.…”
Section: Synthesis Of Ahighly Fluorinatedb Is(binaphthyl Probementioning
confidence: 99%
“…[7] Recently,w ef ound that ab is(binaphthyl)-based fluorescent probe can carry out highly enantioselective fluorescent recognition of amino acids in acetonitrile solution. [8,9] On the basis of this work, we have synthesized af luorophilic probe by incor-porating ah ighly fluorinated alkyl chain. We have demonstrated that in ab iphasic aqueous/fluorous system, the probe can carry out highly enantioselective fluorescent detection of amino acids by selectively extracting the substrates from the aqueous phase into the fluorous phase.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] Certain chromophores, such as spiropyran, azobenzene and diarylethene are well known molecular switches, which can be well utilized to develop photo-responsive chiral supramolecular systems. [19][20][21][22][23] However, recognition of the chiral drugs with the photoresponsive system were usually focused only on the molecular level, [24][25][26][27][28][29] while macroscopic recognition of drugs with the photo-responsive system is a challenging task. [30][31] Even though such a challenge can be overcome by designing a system that can form an effect of enantioselective host-guest complex with the drug molecule.…”
mentioning
confidence: 99%